PENERAPAN METODE REQA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA PADA MATERI MEMBUAT DAN MENJAWAB PERTANYAAN DARI TEKS YANG DIBACA - Kahfi, Riana; Sunarya, Dede Tatang; Karlina, Detty Amelia (Jurnal Pena Ilmiah, 2017)
The research was conducted based on the problems found in the third grade of SDN Rancakendal, Rancaekek subdistrict, on the material about making and answering questions from the text that was read. Students feel difficulty in making and answering questions from text that was read by students. So it was designed a learning plan with applying the REQA (REad, Question and Answer) method to solve the problem. This research is a classroom action research with using Kemmis and McTarggart design. it is consisting of four components are done in two cycles, namely cycle I and II. This research uses instruments, teacher performance observation sheets, student activity observation sheets, evaluation questions, field notes, and interview guidelines. there is an increase in student learning outcomes in each cycle. Then, validation was done with using triangulation, member check and expert opinion. Cycle I, performance percentage of teacher planning 88,55%, implementation 83,33%, student activity 83,08% and result of learning make question 52,17% and answer question 56,52%. Cycle II, Thus through the application of the REQA method can improve students' ability in making and answering questions from the text that was read.